PENINGKATAN KOMPETENSI MENGGAMBAR TEKNIK DENGAN MODEL PEMBELAJARAN BLENDED LEARNING BERBASIS WHATSAPP DI KELAS X DPIB A SMK NEGERI 1 PAJANGAN BANTUL - Wibowo, Andrianto Hari (INCARE, International Journal of Educational Resources, 2022)
This research is backgrounded by the lack of optimal competence of students in drawing techniques in the subject of Technical Drawing. This study aims to: 1) to find out the learning process of students drawing techniques in the subject of Engineering Drawing using the Blended Learning learning model, 2) to determine the improvement of student competence which is seen from the aspects of psychomotor and affective abilities of class X DPIB A students drawing techniques on the subject of Engineering Drawings during learning. This research was conducted from January to May 2021 at SMK Negeri 1 Pajangan. The subjects of the study were class X DPIB A as many as 36 students. This research procedure uses 2 cycles each cycle consisting of 3 meetings. Each cycle consists of planning, execution, observation, reflection. Data collection uses student observation sheets, teacher observation sheets in the learning process, practice test sheets to assess the competence of assessment students which are compiled based on student product assessment criteria. Student questionnaires are used to obtain student response data to the WhatsApp-based Blended Learning learning model. An indicator of the success of this study is an increase in student learning outcomes, namely at least complete students. The results showed that the use of a WhatsApp-based Blended Learning learning model can improve the technical drawing competence of class X DPIB A students in the Subject of Technical Drawing. Before implementing the WhatsApp-based Blended Learning learning model, only 25% of students were competent with an average score of 65. After the WhatsApp-based Blended Learning learning model was applied to cycle I competent students increased to 72% with an average score of 79 and there was another increase in cycle II of 100% competent students with an average score of 83.